Fe–N supported on graphitic carbon nano-networks grown from cobalt as oxygen reduction catalysts for low-temperature fuel cells - Negro, Emanuela; Videla, Alessandro H.A. Monteverde; Baglio, Vincenzo; Aricò, Antonino S.; Specchia, Stefania; Koper, Ger J.M. (Applied catalysis. B, Environmental, 2015)
•Fe–N catalyst successfully synthetized on carbon nano-networks grown from Co.•ORR activity increased with Co and Fe content.•Best electrocatalyst had equal content of pyridinic, pyrrolic and graphitic nitrogen.•Maximum power in PEM/DMFC comparable to the state-of-the-art non-noble catalysts. Three iron–nitrogen-containing non-noble metal electrocatalysts supported on networked graphitic structures, carbon nano-networks (CNNs), were synthesized using a wet-impregnation method. The CNN supports were produced in-house by chemical vapor deposition of ethene over cobalt nanoparticles that were previously synthesized in bicontinuous microemulsions. The three CNN supports differed in cobalt content, ranging from 0.1 to 1.7% in weight. These CNN supports were used to prepare Fe–N/CNN electrocatalysts. The oxygen reduction reaction (ORR) activity was evaluated by rotating disk electrode measurements. Interestingly, the highest ORR activity belonged to the catalyst with the highest iron and cobalt content. The most promising catalyst was investigated as the cathode material in a polymer electrolyte membrane fuel cell (PEMFC) and a direct methanol fuel cell (DMFC). The maximum recorded power densities were 121mWcm−2 for PEMFC and 15mWcm−2 for DMFC, respectively. These values are superior or comparable to the best state of the art for similar materials. The durability to potential cycling was tested in half-cell studies and an activity loss around 10% was found after 1000 cycles, which is not significantly different from what is reported in the literature. The relatively simple synthesis approach and the cheap precursor materials make this electrocatalyst promising for low-temperature fuel cell applications.